Religijność i moralność polskiej młodzieży – zależność czy autonomia? - Boguszewski, Rafał; Bożewicz, Marta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The article is based on the results of current empirical quantitative research carried out on national samples, but also on the results of cyclical research conducted among young people graduating from secondary schools, and focuses on the transformations in the area of religiousness and morality of Polish youth, placing the observed trends on the level of sociological theories of transformations of religiousness and its relation to morality.